Conference report: opportunity and challenge in wood drying: Quality control and energy saving - Pang, Shusheng; Gu, Lianbai (Maderas. Ciencia y Tecnología, 2025)
The 9th IUFRO (International Union of Forestry Organisation) International Wood Drying Conference was held in August 21-26, 2005, in Nanjing, China. It attracted over 120 from 24 countries. At the conference, 58 papers were orally presented and 31 papers were presented as posters. This conference was another success following the eight previous conferences held, respectively, in Skelleftea (Sweden) in 1987, Seattle (USA) in 1999, Vienna (Austria) in 1992, Rotorua (New Zealand) in 1994, Quebec (Canada) in 1996, Stellenbosch (South Africa) in 1999, Tsukuba (Japan) in 2001 and Brasov (Romania) in 2003. The papers presented at the 9th IUFRO International Wood Drying Conference reflected the latest progresses and achievements in wood drying research and development. These papers covered fundamental research (heat and mass transfer, stress development and modelling), new technology development (microwave/radio frequency drying, vacuum drying) and drying related wood properties. The highlight was the research on quality control and energy saving which was the theme of the conference and attracted 14 papers orally presented.